Pelestarian Material Bambu Pada Bangunan Terhadap Konservasi Arsitektur Tradisional Desa Wisata Penglipuran, Bangli: Pelestarian Bambu pada Bangunan - Made Dwi Arya Damautami; Himalaya; Anak Agung Ayu Amitha Dewi; I Kadek Aditya Adi Laksana (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Penglipuran Tourism Village, located in Bangli, Indonesia, is known for the beauty and originality of its traditional architecture. Bamboo has been the main construction material in building houses and structures in this village. Traditional traditional houses in Penglipuran tourist village, Bangli, have the characteristic of similar traditional architectural forms and are neatly arranged, from the main end of the village to the downstream. Traditional houses in Penglipuran village still use building architecture and materials originating from nature where land management there carries the concept of Balinese philosophy, namely Tri Hita Karana which means the balance of human relations with God, humans and the natural surroundings, and humans and humans. Therefore, this journal aims to explore the importance of preserving bamboo materials in the context of conservation of the traditional architecture of Penglipuran Tourism Village, Bangli.